Adopcion temprana de Arachis pintoi en el tropico humedo: el caso de los sistemas ganaderos de doble proposito en el Caqueta, Colombia. (Early adoption of Arachis pintoi in the humid tropics: the case of dual purpose livestock systems in Caqueta, Colombia) - Rivas Ríos, Libardo; Holmann, Federico J. (1999)
The Caqueta region of Colombia is representative of the environmental and economic conditions prevailing in most of Colombia's Amazon region. The department of Caqueta, located in the Amazon River basin, occupies an area of 8.9 million hectares, most of it under jungle. The average annual rainfall is 3500 mm, with an annual relative humidity of 80.7 percent . Dual-purpose production systems can be found on 87 percent of the farms in the region, and 86 percent of the total area is planted to improved pastures. In 1997, the early adoption process of the legume Arachis pintoi, cMani Forrajero Perenne, was studied. Sampling was carried out on farms within the area of influence of Nestle de Colombia. Basic data were collected by surveying a sample chosen from all the farms supplying milk to the Nestle plant in Caqueta. A combined survey strategy was used, with two sample groups. The first was a completely randomized sample, whose size was determined through conventional statistical methods (variance of farm milk production and assumption of different levels of confidence and permissible margins of error). A total of 174 farms were included. The level of confidence was between 80 percent and 85 percent . Because the adoption of this technology is still very recent, for the second group a further survey was made of 52 farms that were using the new forage material. Results are discussed.